2006
DOI: 10.1002/jmri.20717
|View full text |Cite
|
Sign up to set email alerts
|

Automated perfusion‐weighted MRI using localized arterial input functions

Abstract: Purpose: To investigate the utility of an automated perfusion-weighted MRI (PWI) method for estimating cerebral blood flow (CBF) based on localized arterial input functions (AIFs) as compared to the standard method of manual global AIF selection, which is prone to deconvolution errors due to the effects of delay and dispersion of the contrast bolus. Materials and Methods:Analysis was performed on spinand gradient-echo EPI images from 36 stroke patients. A local AIF algorithm created an AIF for every voxel in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 16 publications
0
41
0
2
Order By: Relevance
“…In this study we validated the bookend approach for quantifying CBF against (31)(32)(33)(34) has shown promising results for reducing these errors through selected localized AIFs near the perfused capillary bed and AIF correction models that utilize more accurate bolus arrival times and reduce delay-dependent dispersion. Our study showed a difference in MR-PET correlation slopes based on clinical indication-carotid versus intracranial vessel occlusions-suggesting the need for the incorporation of such models.…”
Section: Discussionmentioning
confidence: 98%
“…In this study we validated the bookend approach for quantifying CBF against (31)(32)(33)(34) has shown promising results for reducing these errors through selected localized AIFs near the perfused capillary bed and AIF correction models that utilize more accurate bolus arrival times and reduce delay-dependent dispersion. Our study showed a difference in MR-PET correlation slopes based on clinical indication-carotid versus intracranial vessel occlusions-suggesting the need for the incorporation of such models.…”
Section: Discussionmentioning
confidence: 98%
“…Initial attempts to measure a local AIF were problematic due to partial volume effects. 29,30 More recently, automated local AIF selection algorithms for MRP have yielded promising results, 31,32 though experience with CTP is lacking. Alternatively, independent component analysis can be used as a tool to define the local AIF.…”
Section: Methods Of Correcting For Delay and Dispersion Of The Aifmentioning
confidence: 99%
“…Unfortunately, there is no ethical and accepted way to define a gold standard perfusion metric in humans. Previous work has shown the utility of the local-AIF approach for predicting tissue outcome poststroke (6). In this study we investigate whether the local-AIF method is achieving its theoretical function, that is, if it is increasing blood flow estimates (relative to the global-AIF method) in voxels with D/D.…”
mentioning
confidence: 97%
“…One method is to use a delay-insensitive deconvolution approach (4). Another method that has shown potential is the local-AIF method (5,6). In this approach, an AIF is defined for each voxel based on the voxels local to it.…”
mentioning
confidence: 99%